1996
DOI: 10.1084/jem.183.5.2397
|View full text |Cite
|
Sign up to set email alerts
|

RANTES and macrophage inflammatory protein 1 alpha selectively enhance immunoglobulin (IgE) and IgG4 production by human B cells.

Abstract: SummaryWe studied the effects of various chemokines including neutrophil-activating peptide 2 (NAP-2), , platelet factor 4 (PF-4), melanoma growth stimulating activity (GRO), ~/interferon-induced protein (IP-10), regulated on activation, normal T expressed and secreted (RANTES), macrophage inflammatory protein lot (MIP-lot), MIP-1 [3, and monocyte chemotactic protein 1 (MCP-1) on Immunoglobulin (IgE) and IgG4 production by human B cells. None of these chemokines with or without interleukin (IL-4), anti-CD40 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…Recently, it has been shown that RANTES and MIP-1␣ can enhance IgE and IgG4 production by IL-4 and anti-CD40 or anti-CD58 mAb-stimulated human sIgE ϩ and sIgG4 ϩ B cells (57). One could suggest that these effects observed in vitro with human B cell IgG4 and IgE responses do not reflect how RANTES affects host immune responses in vivo.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, it has been shown that RANTES and MIP-1␣ can enhance IgE and IgG4 production by IL-4 and anti-CD40 or anti-CD58 mAb-stimulated human sIgE ϩ and sIgG4 ϩ B cells (57). One could suggest that these effects observed in vitro with human B cell IgG4 and IgE responses do not reflect how RANTES affects host immune responses in vivo.…”
Section: Discussionmentioning
confidence: 74%
“…Some bystander effects on the CD123 Ϫ MDC-containing fraction were also observed. More strikingly, cells from ISS-ODN-injected LNs spontaneously secreted elevated levels of cytokines and chemokines (upon culture) that would promote DC and B cell activation in addition to the recruitment of leukocytes into the lymphoid tissues to favor cell-cell communication critical for effective immune activation (48,(91)(92)(93)(94)(95)(96). This is similar to the report in humans describing elevated serum chemokine levels following s.c. injection of a CpG-B ISS-ODN (97).…”
Section: Discussionmentioning
confidence: 99%
“…RANTES is expressed in activated T lymphocytes, airway epithelial cells, platelets, fibroblasts, and renal epithelial and mesangial cells [6]. RANTES has also been shown to enhance the production of IgE and IgG4 by activated B cells [7]. In addition, RANTES recruits eosinophils and T cells into the airways during asthma [8] and allergic airway disease [9] and it may contribute to their immunopathology [10].…”
Section: Introductionmentioning
confidence: 99%